High-entropy fluorophosphate-doped sodium vanadium oxide positive electrode material and preparation method thereof
Patent Information
- Application Number
- CN202610686708.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-19
- Publication Date
- 2026-10-20
AI Technical Summary
该工艺仅回收了钒元素,而废料中大量伴生的其他过渡金属元素未被利用,通常作为废弃物排放,造成资源浪费和潜在环境污染
[0016]与现有技术相比,本发明的有益效果包含以下中的至少一项:
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of cathode materials for sodium-ion batteries, and more specifically, to a high-entropy doped sodium vanadium fluorophosphate cathode material and its preparation method. Background Technology
[0002] Lithium-ion batteries have gained dominance due to their advantages such as high operating voltage, high specific energy, long lifespan, low self-discharge rate, and wide temperature range, and are widely used in various portable electronic products, electric vehicle technology, and other fields. However, the scarcity and uneven distribution of lithium resources have led to a sharp rise in the price of lithium-ion batteries and resource shortages, thus limiting their application in large-scale static energy storage. Sodium, like lithium, belongs to Group IA of the periodic table and has very similar physical and chemical properties. Furthermore, sodium is abundant (2.74% of the Earth's crust, approximately 350 times that of lithium), widely distributed, and inexpensive. Therefore, sodium-ion batteries possess many unique advantages, including low cost, abundant resources, long cycle life, and high safety, making them extremely promising for large-scale power storage.
[0003] Cathode materials are a core component of sodium-ion batteries. To meet the requirements of practical applications, ideal cathode materials should possess characteristics such as low cost, good stability, high redox potential, and high specific capacity. Polyanionic compounds are three-dimensional frameworks constructed from anionic polyhedral structural units through shared points / edges. Compared to oxide systems and Prussian blue analogue systems, they have significant advantages such as structural stability, fast ion transport, and high redox potential. Among them, NASICON-type sodium vanadium fluorophosphate (Na3V2(PO4)2F3) has a three-dimensional structure, which is conducive to the migration of Na⁺. In addition, this material has an average operating voltage of 3.95V and an energy density as high as 507 Wh / kg, comparable to commercial LiFePO4 material (530 Wh / kg), showing broad application prospects. However, sodium vanadium fluorophosphate cathode materials suffer from poor intrinsic electronic conductivity and low ion diffusion rate, resulting in poor rate performance.
[0004] Meanwhile, the amount of vanadium-containing waste generated is enormous. Typical vanadium-containing waste includes: spent vanadium catalysts (V₂O₅ content can reach 8%~20%) from petroleum refining or sulfuric acid industry, vanadium-containing steel slag and vanadium extraction waste from iron and steel metallurgy, waste sodium-ion battery cathode materials, and waste vanadium electrolyte. In addition to vanadium, the above-mentioned wastes often contain various transition metal elements (such as Fe, Al, Ti, W, As, etc.). Currently, the mainstream process for recovering vanadium from vanadium-containing waste is the "roasting-leaching-vanadium precipitation-calcination" route, which ultimately yields V₂O₅ or NH₄VO₃ products. This process only recovers vanadium, while the large amount of other transition metal elements associated with the waste are not utilized and are usually discharged as waste, causing resource waste and potential environmental pollution.
[0005] Therefore, there is an urgent need to develop a method that can simultaneously utilize vanadium and various associated metal ions in vanadium-containing waste, simplify the process, reduce production costs, and directly prepare high-performance sodium vanadium fluorophosphate cathode materials. Summary of the Invention
[0006] In view of the shortcomings of the prior art, one of the objectives of this invention is to solve one or more problems existing in the prior art. For example, one objective of this invention is to provide a method that can comprehensively utilize vanadium and various associated metal ions in vanadium-containing waste, with a simple process flow, and can prepare high-performance, high-entropy doped sodium vanadium fluorophosphate cathode materials.
[0007] To achieve the above objectives, the present invention provides a method for preparing high-entropy doped sodium vanadium fluorophosphate cathode material, which may include the following steps: pretreating vanadium-containing waste to obtain a leachate containing vanadium and doped metal ions; configuring the leachate to satisfy the chemical formula Na3V for high-entropy doped sodium vanadium fluorophosphate cathode material. 2-x M x The stoichiometric ratio of (PO4)2F3 / C is given, where 0.1 ≤ x ≤ 1, and M is a dopant metal, which can be selected from at least three of Fe, Al, Ti, W, As, Ni, Mg, Mn, Cr and Co; the prepared mixture is shaped to obtain a carbon-containing precursor; the carbon-containing precursor is dried, ground, and calcined under an inert or reducing atmosphere to obtain a carbon-coated high-entropy doped sodium vanadium fluorophosphate cathode material.
[0008] Furthermore, the molding process of the prepared mixture may include: adjusting the pH of the mixture to 6-8 with citric acid or ethylenediaminetetraacetic acid as a complexing agent under stirring in a water bath at 50 ℃ to 90 ℃, and continuing to stir for 1-6 hours until a transparent gel is formed to obtain a gel-like precursor.
[0009] Further, the molding process of the prepared mixture may include: adding a carbon source to the mixture, heating to 50 ℃~80 ℃ and stirring continuously; using ammonia or sodium hydroxide solution as a precipitant to adjust the pH of the system to 6.5~8.0, so that the metal ions in the mixture form co-precipitates with phosphate and fluoride ions; after precipitation, continue stirring and aging for 2~6 hours, let stand, collect the precipitate, wash, dry, and obtain a powdered precursor.
[0010] Furthermore, the vanadium-containing waste can be selected from one or more of the following: vanadium-containing catalyst waste, vanadium extraction slag, vanadium-containing steel slag, waste sodium-ion battery cathode waste, and waste vanadium electrolyte. Among these, the vanadium-containing catalyst waste can be from petroleum refining or the sulfuric acid industry. The vanadium-containing steel slag can be the tailings from the vanadium extraction slag processed by the sodium roasting process.
[0011] Furthermore, the pretreatment of vanadium-containing waste may include: crushing, grinding, acid leaching, and filtering the vanadium-containing waste to obtain a leaching solution containing vanadium and doped metal ions. The acid leaching solution is at least one of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, and perchloric acid. The leaching temperature is 25 ℃ to 100 ℃, the leaching time is 1 to 6 hours, and the solid-liquid ratio of the vanadium-containing waste to the acid leaching solution is 1:(10 to 50).
[0012] Furthermore, the preparation of the leachate may include: if the content of sodium, phosphorus and / or fluorine in the leachate is insufficient, adding a sodium source, a phosphorus source and / or a fluorine source to the leachate, wherein the sodium source is selected from one or more of sodium carbonate, sodium hydroxide, sodium acetate, sodium nitrate and sodium fluoride; the phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and sodium phosphate; and the fluorine source is selected from one or more of sodium fluoride, ammonium fluoride and ammonium hydrogen fluoride.
[0013] Furthermore, the calcination can be carried out in two stages. The first stage of calcination may include pre-calcining at a heating rate of 1 ℃ / min to 10 ℃ / min to 300 ℃ to 450 ℃ for 1 to 6 hours; the second stage of calcination may include calcining at a high temperature of 500 ℃ to 800 ℃ at a heating rate of 2 ℃ / min to 10 ℃ / min for 6 to 12 hours.
[0014] Another aspect of the present invention provides a high-entropy doped sodium vanadium fluorophosphate cathode material, which can be prepared by the high-entropy doped sodium vanadium fluorophosphate cathode material preparation method described above.
[0015] Another aspect of the present invention provides a sodium-ion battery that may include the high-entropy doped sodium vanadium fluorophosphate cathode material described above.
[0016] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:
[0017] (1) This invention uses vanadium-containing waste as raw material and employs an integrated process of "leaching-component regulation-forming treatment-calcination" to prepare carbon-coated high-entropy doped sodium vanadium fluorophosphate cathode material. Compared with the preparation process of first precipitating vanadium, calcining to obtain pure V2O5, and then re-blending with various high-purity metal salts, the method of this invention eliminates the lengthy intermediate steps of vanadium extraction product preparation and purification, shortening the process by more than 50% and reducing overall energy consumption by more than 40%. At the same time, it directly utilizes at least three transition metal ions associated with the waste as high-entropy doping elements, reducing raw material costs by 60%–80% compared to the preparation route that uses all high-purity chemical reagents.
[0018] (2) This invention directly transforms vanadium-containing waste (such as spent vanadium catalysts, vanadium extraction slag, vanadium-containing steel slag, etc.), which was previously only used as raw material for vanadium extraction or was difficult to process, into high-performance sodium-ion battery cathode materials, turning waste into treasure. The associated metal ions (such as Fe, Al, Ti, W, As, etc.) that originally required multiple separation and removal steps in the waste are transformed in situ into high-entropy doped functional components, avoiding resource waste and secondary pollution. This "waste-to-material" strategy significantly reduces the environmental pressure of waste treatment and opens up a new path for the high-value utilization of vanadium-containing waste.
[0019] (3) In the cathode material prepared by the present invention, high-entropy doped sodium vanadium fluorophosphate particles are uniformly coated inside the porous carbon material. The carbon coating layer protects the surface of the active particles and improves the interfacial stability between the material and the electrolyte. At the same time, the lattice distortion and entropy stabilization effect brought about by multi-element high-entropy doping makes the material have smaller volume changes, more reversible phase changes, and fewer cracks / pulverizations during charging and discharging, and the long-cycle capacity retention rate of the material is significantly improved.
[0020] (4) This invention utilizes high-entropy design to reduce the sodium ion migration energy barrier, thereby reducing phase transitions during charging and discharging and making the internal dynamics of the electrode more uniform. Simultaneously, carbon coating enhances the overall electronic conductivity. Thanks to the aforementioned synergistic effect, the carbon-coated high-entropy doped sodium fluorophosphate cathode material of this invention maintains excellent capacity output under high-rate conditions, with rate performance significantly superior to undoped or single-element doped sodium fluorophosphate materials.
[0021] (5) The carbon-coated high-entropy doped sodium vanadium fluorophosphate cathode material prepared by the present invention is applied in the field of sodium-ion secondary batteries. It has both high rate performance and long cycle life, and has broad application prospects. It is especially suitable for large-scale power storage fields with high requirements for cost and life. Detailed Implementation
[0022] In the following, a high-entropy doped sodium vanadium fluorophosphate cathode material and its method according to the present invention will be described in detail with reference to exemplary embodiments.
[0023] One aspect of the present invention provides a method for preparing a high-entropy doped sodium vanadium fluorophosphate cathode material. In some embodiments, the method may include the following steps:
[0024] Step 1: Pre-treat the vanadium-containing waste to obtain a leachate containing vanadium and doped metal ions;
[0025] Step 2: Prepare the leachate so that each component satisfies the chemical formula Na3V for high-entropy doped sodium vanadium fluorophosphate cathode material. 2-x M x The stoichiometric ratio of (PO4)2F3 / C, wherein 0.1 ≤ x ≤ 1, and M is a doped metal, which can be selected from at least three of Fe, Al, Ti, W, As, Ni, Mg, Mn, Cr and Co;
[0026] Step 3: The mixture after the components are prepared is subjected to molding treatment to obtain a carbon-containing precursor;
[0027] Step 4: Dry and grind the carbon-containing precursor, then calcine it under an inert or reducing atmosphere to obtain a carbon-coated high-entropy doped sodium vanadium fluorophosphate cathode material with the general chemical formula Na3V. 2-x M x (PO4)2F3 / C.
[0028] In some implementations, the vanadium-containing waste can be waste containing vanadium, sodium, transition metals, phosphorus, and fluorine. The transition metal, used as the dopant metal in the sodium vanadium fluorophosphate cathode material, can be selected from at least three of Fe, Al, Ti, W, As, Ni, Mg, Mn, Cr, and Co. For example, it can be selected from four, five, or six of Fe, Al, Ti, W, As, Ni, Mg, Mn, Cr, and Co. The vanadium-containing waste can be selected from one or more of waste vanadium catalysts, vanadium extraction slag, vanadium-containing steel slag, waste sodium-ion battery cathode material, and waste vanadium electrolyte. For example, the waste vanadium catalyst can be a waste vanadium catalyst from petroleum refining or the sulfuric acid industry. The vanadium-containing steel slag can be the tailings after vanadium extraction slag is processed using the sodium roasting process.
[0029] In some embodiments, pretreatment of vanadium-containing waste may include: crushing and grinding the vanadium-containing waste, leaching it with an acidic leachate, and filtering it after leaching to obtain a leachate containing vanadium and doped metal ions. In some embodiments, the acidic leachate may be at least one of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, and perchloric acid. The concentration of the acidic leachate may be 10–75%. The leaching temperature may be 25 °C–100 °C, and the leaching time may be 1–6 hours. For example, the leaching temperature may be 32 °C–90 °C, and the leaching time may be 2–5 hours. Another example is that the leaching temperature may be 45 °C–78 °C, and the leaching time may be 3–4 hours. The solid-liquid ratio of the vanadium-containing waste to the acidic leachate may be 1:(10–50). For example, the solid-liquid ratio of the vanadium-containing waste to the acidic leachate may be 1:(16–42), 1:(22–30), or a combination thereof.
[0030] In some implementation schemes, the high-entropy doped sodium vanadium fluorophosphate cathode material can be produced according to the general chemical formula Na3V. 2-x M x The raw material components are configured in a stoichiometric ratio for (PO4)2F3 / C, wherein 0.1 ≤ x ≤ 1, and M is a dopant metal selected from at least three of Fe, Al, Ti, W, As, Ni, Mg, Mn, Cr, and Co. When the sodium, phosphorus, and / or fluorine content in the leachate is insufficient, the corresponding substances can be added according to the stoichiometric ratio. In some embodiments, the sodium source can be selected from one or more of sodium carbonate, sodium hydroxide, sodium acetate, sodium nitrate, and sodium fluoride. The phosphorus source can be selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and sodium phosphate. The fluorine source can be selected from one or more of sodium fluoride, ammonium fluoride, and ammonium hydrogen fluoride. Of course, if the V and dopant metal in the leachate are insufficient, a V source or a dopant metal source can also be added. In some embodiments, the total sodium ion to (vanadium + dopant metal) molar ratio can be (3.0–4.0):(1.8–2.2). The molar ratio of phosphorus to (vanadium + doped metal) can be (2.0–2.2):(1.8–2.2). The molar ratio of fluorine to vanadium can be (3.0–4.0):(2.0–2.2).
[0031] In some implementation schemes, inductively coupled plasma optical emission spectroscopy (ICP-OES) or atomic absorption spectroscopy (AAS) can be used to determine the concentration of each component in the leachate, and based on the measurement results, it can be determined whether to add the corresponding substances to meet the preset stoichiometric ratio of high-entropy doped sodium fluorophosphate.
[0032] In some implementations, shaping the mixture after configuring the components may include:
[0033] Under stirring in a water bath at 50℃~90℃, the pH of the mixture is adjusted to 6~8 using citric acid or ethylenediaminetetraacetic acid as a complexing agent, and stirring is continued for 1~6 hours until a transparent gel is formed, yielding a gel-like precursor. For example, under stirring in a water bath at 55℃~75℃, the pH of the mixture is adjusted to 7 using citric acid as a complexing agent, and stirring is continued for 2~4 hours until a transparent gel is formed, yielding a gel-like precursor. In this case, the complexing agent can serve as a carbon source, which, after calcination, enables carbon coating of the high-entropy doped sodium vanadium fluorophosphate cathode material.
[0034] In some implementations, shaping the mixture after configuring the components may include:
[0035] Step 301: Add a carbon source to the mixture, heat to 50℃~80℃ and stir continuously. Use ammonia or sodium hydroxide solution as a precipitant to adjust the pH of the system to 6.5~8.0, so that the metal ions in the mixture form a co-precipitate with phosphate and fluoride ions. In some embodiments, adding a carbon source to the mixture can achieve carbon coating of the high-entropy doped sodium vanadium fluorophosphate cathode material after calcination. For example, the carbon source can be one or more of glucose, sucrose, and fructose. In some embodiments, after adding the carbon source, the mixture can be heated to 55℃~73℃ or 62℃~68℃ and stirred continuously, and a precipitant can be added to adjust the pH of the system to a combination of 7.2~7.8, 7.4~7.6, or higher, so that the metal ions in the mixture form a co-precipitate with phosphate and fluoride ions.
[0036] Step 302: After precipitation, continue stirring and aging for 2–6 hours, let stand, collect the precipitate, wash, and dry to obtain a powdered precursor. In some embodiments, after the precipitant is added dropwise, continue stirring and aging for 3–5 hours, let stand overnight, filter or centrifuge to collect the precipitate, wash 2–3 times each with deionized water and anhydrous ethanol; place the obtained precipitate in an oven at 80–120°C and dry for 10–24 hours to obtain the precursor powder.
[0037] In some implementations, calcination can be performed in two stages. For example, the temperature can be raised to 300°C–450°C at a rate of 1°C / min–10°C / min for 1–6 hours to allow the moisture and organic matter in the precursor to fully evaporate and complete the initial phase formation, thus completing the first stage of calcination. Then, the temperature can be raised to 500°C–800°C at a rate of 2°C / min–10°C / min for 6–12 hours to achieve the second stage of calcination. For example, the temperature can be raised to 350°C–420°C at a rate of 3°C / min–8°C / min for 2–5 hours to allow the moisture and organic matter in the precursor to fully evaporate and complete the initial phase formation; then, the temperature can be raised to 530°C–740°C at a rate of 4°C / min–8°C / min for 7–11 hours to achieve the second stage of calcination. For example, the temperature can be raised to 380℃ to 400℃ at a heating rate of 5℃ / min to 7℃ / min for 3 to 4 hours to allow the moisture and organic matter in the precursor to fully evaporate and complete the initial phase formation; then the temperature can be raised to 560℃ to 680℃ at a heating rate of 5℃ / min to 7℃ / min for calcination for 8 to 10 hours.
[0038] In some implementations, the inert gas can be nitrogen and / or argon. The reducing atmosphere can be a hydrogen-argon mixture, wherein the hydrogen volume percentage can be 5% to 10%.
[0039] To better understand the present invention, specific examples are provided below to further illustrate the content of the present invention, but the content of the present invention is not limited to the examples below.
[0040] Example 1
[0041] A method for preparing a high-entropy doped sodium vanadium fluorophosphate cathode material includes the following steps:
[0042] Step 1: Take 10g of waste vanadium catalyst, crush and grind it, then add 100ml of 30% sulfuric acid leaching solution at a solid-liquid ratio of 1:10 for leaching. After leaching at 40℃ for 3 hours, filter to obtain the leaching solution.
[0043] Step 2: Analyze the composition of the leachate using atomic absorption spectroscopy (AAS), adjust the molar ratio of V, Al, Fe, and As in the solution to 1.85:0.05:0.05:0.05, and then add ammonium dihydrogen phosphate, sodium fluoride, and sodium carbonate to make n(Na):n(V+doped metal) = 3:2, n(P):n(V+doped metal) = 2:2, and n(F):n(V) = 3:2 to obtain a mixed solution.
[0044] Step 3: Add citric acid and adjust the pH to 7 with ammonia water. Stir in a 75°C water bath to form a gel and dry to obtain a gel-like precursor.
[0045] Step 4: Pre-calcine at 400℃ for 3 hours under an argon atmosphere, then calcine at 700℃ for 10 hours to obtain carbon-coated high-entropy doped sodium vanadium fluorophosphate cathode material.
[0046] The carbon-coated high-entropy sodium vanadium fluorophosphate cathode material obtained above was mixed with conductive agent Super P and binder PVDF at a mass ratio of 8:1:1. After grinding evenly, an appropriate amount of NMP was added to prepare a mixed slurry. The slurry was then evenly coated onto aluminum foil with a scraper and placed in a vacuum drying oven at 120℃ for 8 hours. The electrode sheet was then rolled and stamped to obtain a 14 mm electrode sheet. A sodium metal sheet was used as a control electrode. The electrolyte system was 1M NaClO4 / PC:FEC (95:5), glass fiber was used as the separator, and CR2025 stainless steel was used as the battery shell. Finally, 2025 button half-cells were assembled in a super-clean glove box. The electrochemical performance was tested in the voltage range of 2 to 4.5V at 1C = 126 mA / g. The capacity retention rate after 100 cycles at 1C was measured to be 92.4%.
[0047] Example 2
[0048] A method for preparing a high-entropy doped sodium vanadium fluorophosphate cathode material includes the following steps:
[0049] Step 1: Take 10g of waste vanadium catalyst, crush and grind it, then add 100ml of 30% sulfuric acid leaching solution at a solid-liquid ratio of 1:10 for leaching. After leaching at 40℃ for 3 hours, filter to obtain the leaching solution.
[0050] Step 2: Analyze the composition of the leachate using atomic absorption spectrometry (AAS), adjust the molar ratio of V, Al, Fe, As, and W in the solution to 1.8:0.05:0.05:0.05:0.05, and then add ammonium dihydrogen phosphate, sodium fluoride, and sodium carbonate to make n(Na):n(V+doped metal) = 3:2, n(P):n(V+doped metal) = 2:2, and n(F):n(V) = 3:2 to obtain a mixed solution.
[0051] Step 3: Add citric acid and adjust the pH to 8 with ammonia water. Stir in a 90°C water bath to form a sol, and dry to obtain a gel-like precursor.
[0052] Step 4: Pre-calcine at 450°C for 5 hours under an argon atmosphere, then calcine at 500°C for 12 hours to obtain carbon-coated high-entropy doped sodium vanadium fluorophosphate cathode material.
[0053] The carbon-coated high-entropy sodium vanadium fluorophosphate cathode material obtained above was mixed with super P and PVDF at a mass ratio of 8:1:1. After grinding evenly, an appropriate amount of NMP was added dropwise to prepare a mixed slurry. The slurry was then evenly coated onto aluminum foil with a scraper and placed in a vacuum drying oven at 120℃ for 8 hours. The electrode was then rolled and stamped to obtain a 14 mm electrode. Finally, a 2025 button half-cell was assembled in a super-clean glove box. Its electrochemical performance was tested in the voltage range of 2 to 4.5V at 1C = 127.1 mA / g. The capacity retention rate after 100 cycles under 1C conditions was measured to be 94.1%.
[0054] Example 3
[0055] A method for preparing a high-entropy doped sodium vanadium fluorophosphate cathode material includes the following steps:
[0056] Step 1: Take 10g of waste vanadium catalyst, crush and grind it, then add 100ml of 30% sulfuric acid leaching solution at a solid-liquid ratio of 1:10 for leaching. After leaching at 40℃ for 3 hours, filter to obtain the leaching solution.
[0057] Step 2: Analyze the composition of the leachate using atomic absorption spectrometry (AAS), adjust the molar ratio of V, Al, Fe, As, W, and Ti in the solution to 1.75:0.05:0.05:0.05:0.05:0.05, and then add ammonium dihydrogen phosphate, sodium fluoride, and sodium carbonate to make n(Na):n(V+doped metal) = 3:2, n(P):n(V+doped metal) = 2:2, and n(F):n(V) = 3:2 to obtain a mixed solution.
[0058] Step 3: Add citric acid and adjust the pH to 6 with ammonia water. Stir in a 55°C water bath to form a sol, and dry to obtain a dry gel.
[0059] Step 4: Pre-calcine at 300℃ for 3 hours under an argon atmosphere, and then calcine at 750℃ for 10 hours to obtain carbon-coated high-entropy doped sodium vanadium fluorophosphate cathode material.
[0060] The carbon-coated high-entropy sodium vanadium fluorophosphate cathode material obtained above was mixed with super P and PVDF at a mass ratio of 8:1:1. After grinding evenly, an appropriate amount of NMP was added dropwise to prepare a mixed slurry. The slurry was then evenly coated onto aluminum foil with a scraper and placed in a vacuum drying oven at 120℃ for 8 hours. The electrode was then rolled and stamped to obtain a 14 mm electrode. Finally, a 2025 button half-cell was assembled in a super-clean glove box. Its electrochemical performance was tested in the voltage range of 2 to 4.5V at 1C = 127.7 mA / g. The capacity retention rate after 100 cycles under 1C conditions was measured to be 93.8%.
[0061] Example 4
[0062] A method for preparing a high-entropy doped sodium vanadium fluorophosphate cathode material includes the following steps:
[0063] Step 1: Take 10g of waste vanadium catalyst, crush and grind it, then add 100ml of 30% sulfuric acid leaching solution at a solid-liquid ratio of 1:10 for leaching. After leaching at 40℃ for 3 hours, filter to obtain the leaching solution.
[0064] Step 2: Analyze the composition of the leachate using atomic absorption spectrometry (AAS), adjust the molar ratio of V, Al, Fe, As, W, and Ti in the solution to 1.75:0.05:0.05:0.05:0.05:0.05, and then add ammonium dihydrogen phosphate, sodium fluoride, and sodium carbonate to make n(Na):n(V+doped metal) = 3:2, n(P):n(V+doped metal) = 2:2, and n(F):n(V) = 3:2 to obtain the mixed solution.
[0065] Step 3: Heat the mixed solution to 65 °C, slowly add 1 mol / L ammonia water dropwise until pH=7.2, continue stirring and aging for 4 hours, filter and wash the precipitate with deionized water and ethanol, dry at 110 °C for 12 hours to obtain the precursor.
[0066] Step 4: Under a 5% H2 / Ar atmosphere, first pre-calcine at 400 °C for 4 hours by heating at 5 °C / min, then calcine at 720 °C for 12 hours by heating at 5 °C / min, and then cool with the furnace to obtain high-entropy doped sodium fluorophosphate.
[0067] The carbon-coated high-entropy sodium vanadium fluorophosphate cathode material obtained above was mixed with super P and PVDF at a mass ratio of 8:1:1. After grinding evenly, an appropriate amount of NMP was added dropwise to prepare a mixed slurry. The slurry was then evenly coated onto aluminum foil with a scraper and placed in a vacuum drying oven at 120 ℃ for 8 h. The electrode was then rolled and stamped to obtain a 14 mm electrode. Finally, a 2025 button half-cell was assembled in a super cleanroom glove box. Its electrochemical performance was tested in the voltage range of 2 to 4.5 V at 1C = 124 mA / g. The capacity retention rate after 100 cycles under 1C conditions was measured to be 90.5%.
[0068] Comparative Example 1
[0069] The difference from Example 1 is that no carbon source citric acid is added during the gelation process in step 3, but the preparation method is the same as in Example 1.
[0070] The same method was used to assemble 2025 coin cells, and their electrochemical performance was tested in the voltage range of 2 to 4.5 V at 1C = 124.3 mA / g. The capacity retention rate after 100 cycles at 1C was found to be 75.8%.
[0071] Comparing Example 1 with Comparative Example 1, it can be found that the high-entropy doped sodium vanadium fluorophosphate cathode material of the present invention utilizes carbon coating, which can improve the capacity retention rate of the material and enhance its chemical properties.
[0072] Comparative Example 2
[0073] Compared with Example 1, the difference is that this comparative example does not use vanadium-containing waste as raw material. Instead, it uses laboratory reagents NaF, NH4VO3, NaH2PO4, Fe(NO3)3, Al(NO3)3, and As(NO3)3 as raw materials. The F, V, P, Fe, Al, and As elements are mixed according to the proportions in Example 1 to obtain a mixed solution. Citric acid is added and the pH is adjusted to 7 with ammonia. The solution is stirred in a water bath at 75 °C to form a sol and dried to obtain a dry gel. The gel is then pre-calcined at 400 °C for 3 hours under an argon atmosphere and then calcined at 700 °C for 10 hours to obtain a carbon-coated high-entropy doped sodium vanadium fluorophosphate cathode material.
[0074] The same method was used to assemble 2025 coin cells, and their electrochemical performance was tested in the voltage range of 2 to 4.5 V at 1C = 115.6 mA / g. The capacity retention rate after 100 cycles under 1C conditions was found to be 88.5%.
[0075] Comparing Example 1 with Comparative Example 1, it can be found that the positive electrode material prepared by the present invention using vanadium-containing waste as raw material has a higher battery capacity retention rate after assembly compared with commercially available products.
[0076] Comparative Example 3
[0077] Compared with Example 1, the difference is that this comparative example does not use vanadium-containing waste as raw material, but uses laboratory reagents NaF, NH4VO3, NaH2PO4, Fe(NO3)3, and Al(NO3)3 as raw materials, and the doping element does not contain As. After mixing the raw materials, citric acid was added and the pH was adjusted to 7 with ammonia water. The mixture was stirred in a water bath at 75 °C to form a gel. Under an argon atmosphere, it was first pre-calcined at 400 °C for 3 hours, and then calcined at 700 °C for 10 hours to obtain a carbon-coated high-entropy doped sodium vanadium fluorophosphate cathode material.
[0078] The same method was used to assemble 2025 coin cells, and their electrochemical performance was tested in the voltage range of 2 to 4.5 V at 1C = 106.9 mA / g. The capacity retention rate after 100 cycles under 1C conditions was found to be 86.7%.
[0079] Comparing Comparative Example 2 (with 3 doping elements) and Comparative Example 3 (with 2 doping elements), both used the same raw materials (commercially available), differing only in the number of doping elements. The results showed that the battery capacity retention rate of Comparative Example 3 was lower than that of Comparative Example 2, indicating that reducing the number of doping elements from 3 to 2 leads to a decrease in retention rate under the same conditions. Next, comparing Example 1 and Comparative Example 2, both used the same number of doping elements, differing only in the source of the raw materials. The results showed that the battery capacity retention rate of Example 1 was higher than that of Comparative Example 2. Therefore, it can be shown that fewer than 3 doping elements (Comparative Example 3) leads to a decrease in retention rate, and the 3-doped material prepared using vanadium-containing waste as raw material in this invention exhibits superior performance.
[0080] Comparative Example 4
[0081] Compared with Example 1, the difference is that this comparative example does not use vanadium-containing waste as raw material, but uses laboratory reagents NaF, NH4VO3, NaH2PO4, and Fe(NO3)3 as raw materials, and the doping elements do not include Al and As. After mixing the raw materials, citric acid was added and the pH was adjusted to 7 with ammonia water. The mixture was stirred in a water bath at 75 °C to form a sol, and dried to obtain a dry gel. Under an argon atmosphere, the gel was first pre-calcined at 400 °C for 3 hours, and then calcined at 700 °C for 10 hours to obtain a carbon-coated high-entropy doped sodium vanadium fluorophosphate cathode material.
[0082] The same method was used to assemble 2025 coin cells, and their electrochemical performance was tested in the voltage range of 2 to 4.5 V at 1C = 98.4 mA / g. The capacity retention rate after 100 cycles at 1C was found to be 80.2%.
[0083] Similarly, comparative examples 1 and 2-4 show that fewer than 3 doping elements (comparative examples 3 and 4) lead to a decrease in retention rate. Meanwhile, the 3 or more doped materials prepared by the present invention using vanadium-containing waste as raw material have better performance.
[0084] The test results of Examples 1-4 and Comparative Examples 1-4 are shown in Table 1.
[0085] Table 1 Test Results
[0086]
[0087] Although the invention has been described above in conjunction with exemplary embodiments, those skilled in the art will understand that various modifications and changes can be made to the exemplary embodiments of the invention without departing from the spirit and scope defined by the claims.
Claims
1. A method for preparing a high-entropy doped sodium vanadium fluorophosphate cathode material, characterized in that, Includes the following steps: Vanadium-containing waste is pretreated to obtain a leachate containing vanadium and doped metal ions; The components of the leachate are configured to meet the chemical formula Na3V for high-entropy doped sodium vanadium fluorophosphate cathode materials. 2-x M x The stoichiometric ratio of (PO4)2F3 / C is given, where 0.1 ≤ x ≤ 1, and M is a dopant metal selected from at least three of Fe, Al, Ti, W, As, Ni, Mg, Mn, Cr, and Co; the mixture after preparation is subjected to molding treatment to obtain a carbon-containing precursor. The carbon-containing precursor is dried, ground, and calcined under an inert or reducing atmosphere to obtain a carbon-coated high-entropy doped sodium vanadium fluorophosphate cathode material.
2. The method for preparing high-entropy doped sodium vanadium fluorophosphate cathode material according to claim 1, characterized in that, The molding process for the mixture after preparation of components includes: Under stirring in a water bath at 50 ℃~90 ℃, the pH of the mixture is adjusted to 6~8 using citric acid or ethylenediaminetetraacetic acid as a complexing agent, and stirring is continued for 1~6 hours until a transparent gel is formed, thus obtaining a gel-like precursor.
3. The method for preparing high-entropy doped sodium vanadium fluorophosphate cathode material according to claim 1, characterized in that, The molding process for the mixture after preparation of components includes: Add a carbon source to the mixture, heat to 50 ℃~80 ℃ and stir continuously, use ammonia or sodium hydroxide solution as a precipitant, adjust the pH of the system to 6.5~8.0, so that the metal ions in the mixture form co-precipitates with phosphate and fluoride ions; After precipitation, continue stirring and aging for 2-6 hours, let stand, collect the precipitate, wash, dry, and obtain a powdered precursor.
4. The method for preparing high-entropy doped sodium vanadium fluorophosphate cathode material according to any one of claims 1 to 3, characterized in that, Vanadium-containing waste is selected from one or more of the following: vanadium-containing catalyst waste, vanadium extraction slag, vanadium-containing steel slag, waste sodium-ion battery cathode waste, and waste vanadium electrolyte. Among them, the vanadium-containing catalyst waste is vanadium-containing catalyst waste from petroleum refining or sulfuric acid industry; the vanadium-containing steel slag is the tailings after vanadium extraction slag is processed by sodium roasting process.
5. The method for preparing high-entropy doped sodium vanadium fluorophosphate cathode material according to any one of claims 1 to 3, characterized in that, Pretreatment of vanadium-containing waste includes: crushing, grinding, acid leaching, and filtering the vanadium-containing waste to obtain a leachate containing vanadium and doped metal ions. The acid leaching solution is at least one of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid and perchloric acid. The leaching temperature is 25 ℃ to 100 ℃, the leaching time is 1 to 6 hours, and the solid-liquid ratio of vanadium-containing waste to acid leaching solution is 1:(10 to 50).
6. The method for preparing high-entropy doped sodium vanadium fluorophosphate cathode material according to any one of claims 1 to 3, characterized in that, The components of the leachate preparation include: if the sodium, phosphorus, and / or fluorine content in the leachate is insufficient, a sodium source, a phosphorus source, and / or a fluorine source are added to the leachate. The sodium source is selected from one or more of sodium carbonate, sodium hydroxide, sodium acetate, sodium nitrate, and sodium fluoride; The phosphorus source is selected from one or more of phosphoric acid, diammonium dihydrogen phosphate, diammonium hydrogen phosphate, and sodium phosphate; The fluorine source is selected from one or more of sodium fluoride, ammonium fluoride, and hydrogen fluoride.
7. The method for preparing high-entropy doped sodium vanadium fluorophosphate cathode material according to any one of claims 1 to 3, characterized in that, The calcination is carried out in two stages. The first stage of calcination includes pre-calcination at 300℃ to 450℃ for 1 to 6 hours at a heating rate of 1℃ / min to 10℃ / min. The second stage of calcination includes high-temperature calcination at 500℃ to 800℃ for 6 to 12 hours at a heating rate of 2℃ / min to 10℃ / min.
8. A high-entropy doped sodium vanadium fluorophosphate cathode material, characterized in that, It is prepared by the high-entropy doped sodium vanadium fluorophosphate cathode material preparation method according to any one of claims 1 to 7.
9. A sodium-ion battery, characterized in that, It includes the high-entropy doped sodium vanadium fluorophosphate cathode material as described in claim 8.